Cultural Memory and Identity Politics: An Ethnographic Study of Manuscript Preservation Practices at Sanggar Surya Pringga Dermayu, Indramayu - ute lies khadijah; elnovani lusiana; agus rusmana; rully khairul anwar (Universitas Andalas, 2026)
Using six months of participant observation (2024) and in-depth interviews with 15 community members, this research reveals three key findings. First, manuscripts are understood as animate entities with ancestral agency, requiring ritual care rather than technical conservation alone. Second, preservation activities—including transliteration workshops and ritual readings—function as cultural performances where community members actively negotiate contested meanings of